1980
DOI: 10.1007/bf00219918
|View full text |Cite
|
Sign up to set email alerts
|

A scanning electron microscope study of myoepithelial cells in exocrine glands

Abstract: By removing connective tissue components with enzymatic digestion followed by HCl-hydrolysis, myoepithelial cells (MECs) of the terminal portion in a variety of exocrine glands of the rat were examined with the scanning electron microscope. The profile of MECs varied considerably from gland to gland; MECs in the lactating mammary gland have a few long cytoplasmic processes in close contact with those of adjacent cells forming a continuous network around the terminal portion. Those of the exorbital lacrimal gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 21 publications
3
62
1
Order By: Relevance
“…We measured the numbers of fluorescence spots for CX43 in SMG and S E , and we found that the differences between the two glands were statistically significant at p = 0.05. These results may be related to the differences in the ... degree of development and volume of myoepithelial cells shown by SEM (Nagato et al, 1980) in both glands. Our results showing the Presence of many spots of cx43 between myoepithelial cells suggest that coupling to coordinate contraction of myoepithelial cells plays an important role in expelling the viscous materials from the acinar lumen in the SLG.…”
Section: Discussionmentioning
confidence: 86%
“…We measured the numbers of fluorescence spots for CX43 in SMG and S E , and we found that the differences between the two glands were statistically significant at p = 0.05. These results may be related to the differences in the ... degree of development and volume of myoepithelial cells shown by SEM (Nagato et al, 1980) in both glands. Our results showing the Presence of many spots of cx43 between myoepithelial cells suggest that coupling to coordinate contraction of myoepithelial cells plays an important role in expelling the viscous materials from the acinar lumen in the SLG.…”
Section: Discussionmentioning
confidence: 86%
“…After a graded alcohol dehydration and two xylene-clearing stages, the sections were stained with conventional hematoxylin-eosin reagents. For electron microscopy, the mammary glands were processed, embedded, sectioned, and examined using previously described methods (24,51).…”
Section: Generation and Analysis Of Mkl1mentioning
confidence: 99%
“…Comparing the results in this study with those in our previous study, the frequency of CX43 in PGs was definitely lower than that in both submandibular and sublingual glands. It is well established that myoepithelial cells invest only the intercalated ducts in the mature rat PG, although their processes often extend onto adjacent portions of acini and striated ducts [7,19]. Thus, the observed localization of CX43 around the intercalated V.…”
Section: Discussionmentioning
confidence: 93%